1994
DOI: 10.1063/1.467275
|View full text |Cite
|
Sign up to set email alerts
|

Guided-ion beam measurements of N++H2O charge-transfer and chemical reaction channels

Abstract: A guidedion beam study of the hydrogen atom transfer reaction of stateselected N+ 2 with H2 at collision energies ranging from subthermal to 2 eV (c.m.) J. Chem. Phys. 102, 214 (1995); 10.1063/1.469394Chargetransfer reaction of 14,15N+(3 P J )+N2(1Σ+ g ) from thermal to 100 eV. Crossedbeam and scatteringcell guidedion beam experiments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…It is suggested that this discrepancy is due to a weaker electronic coupling with the product H 2 O ϩ Ã -state surface. 10 The O ϩ ϩH 2 O collision system, which is exothermic by only ϳ1 eV, appears to violate the Franck-Condon criterion. In this system, the ground state energy level has essentially zero Franck-Condon overlap with product states at resonance.…”
Section: Dynamics Of Hyperthermal Kr ؉ ؉H 2 O Charge-transfer Collisimentioning
confidence: 98%
See 3 more Smart Citations
“…It is suggested that this discrepancy is due to a weaker electronic coupling with the product H 2 O ϩ Ã -state surface. 10 The O ϩ ϩH 2 O collision system, which is exothermic by only ϳ1 eV, appears to violate the Franck-Condon criterion. In this system, the ground state energy level has essentially zero Franck-Condon overlap with product states at resonance.…”
Section: Dynamics Of Hyperthermal Kr ؉ ؉H 2 O Charge-transfer Collisimentioning
confidence: 98%
“…11,12 In particular, charge-transfer cross sections and product ion internal energy distributions were reported for the collision systems X ϩ ϩH 2 O, where X ϩ ϭO ϩ , 7,8 Ar ϩ , 6,9 N 2 ϩ , 6,9 and N ϩ . 4,10 The Ar ϩ ϩH 2 O and N 2 ϩ ϩH 2 O charge-transfer collision systems provided particularly good insight into the charge-transfer dynamics due to the observation of intense H 2 O ϩ Ã 2 A 1 -X 2 B 1 charge-transfer luminescence. 5,6 These systems are exothermic by ϳ3 eV and generally adhere to both energy resonance and Franck-Condon criteria.…”
Section: Dynamics Of Hyperthermal Kr ؉ ؉H 2 O Charge-transfer Collisimentioning
confidence: 99%
See 2 more Smart Citations
“…A similar observation was made in the reactions of N + (-'S) with H2O, in which the NO + channel, which at low energies proceeded on the exothermic singlet surface, was seen to undergo a sharp rise in cross section at the collision energy corresponding to access to the spin-allowed triplet PES. 19 The spin conservation constraint proved important in the interpretation of the related 0 + + CH4 reaction system.-'' 4 Direct dynamics calculations' revealed that all the minor product channels observed for that system in experiments 4 could be accounted for in spin-allowed reaction pathways. Another result of the 0 + + CH 4 direct dynamics work that may offer insight into the present results is that the calculations show that OH + derives from a stripping mechanism, involving large impact parameters and leading to forward scattered ions.…”
Section: Discussionmentioning
confidence: 99%